Effects of enzymatic hydrolysis on physicochemical property and antioxidant activity of mulberry (Morus atropurpurea Roxb.) leaf protein. Issue 10 (25th August 2021) - Sun, Chongzhen; Shan, Yangwei; Tang, Xin; Han, Duo; Wu, Xiyang; Wu, Hui; Hosseininezhad, Marzieh
Abstract: To improve the antioxidant efficiency of mulberry leaf protein (MLP), alcalase, protamex, papain, flavourzyme, neutrase, and trypsin were used to hydrolyze MLP. The yield of soluble peptides, secondary structures, molecular weight distributions, and antioxidant activities of MLP hydrolysates (MLPHs) were investigated. Results showed that the native MLP was rich in the fraction above 6.5 kDa and was mainly composed of β‐sheets, while MLPHs were abundant in the fractions of 0.3–0.6 kDa and 0.6–6.5 kDa and were mainly composed of disordered coils and β‐folds. Limited hydrolysis of MLP could lead to better antioxidant activity than extensive hydrolysis. After enzymatic hydrolysis, the content of total sugar and total phenol in MLP increased significantly. MLP hydrolysates prepared with neutrase, alcalase, and protamex were preferable to other enzymes. Meanwhile, an enzyme to substrate level of 1% and a hydrolysis time of 2 hr were the optimum conditions to obtain higher antioxidant hydrolysates using neutrase. Abstract : Six different enzymes were used to hydrolyze mulberry leaf protein. The yield of soluble peptides, secondary structures, molecular weight distributions, total sugar and phenol, and antioxidant activity of different hydrolysates (MLPH) were analyzed. MLPH prepared with neutrase, alcalase, and protamex were preferable to other enzymes, and neutrase hydrolysates showed the best antioxidant activity.